Changes in North Atlantic Deep Water strength and bottom water masses during Marine Isotope Stage 3 (45-35kaBP) - Gutjahr, M; Hoogakker, B; Frank, M; McCave, I (2010)
The strength of the North Atlantic Meridional Overturning Circulation during climatically highly variable Marine Isotope Stage (MIS) 3 has attracted much attention in recent years. Here we present high-resolution Nd isotope compositions of past seawater derived from authigenic Fe-Mn oxyhydroxides recovered from drift sediments on the Blake Ridge in the deep western North Atlantic (ODP Leg 172, Site 1060, 3481m water depth). The data cover the period from 45 to 35kaBP, tracing circulation changes during major Heinrich iceberg discharge event 4 (H4, ∼40-39kaBP). The Nd isotope record suggests that there was no northern-source water (NSW) mass like modern NADW at the deeper part of Blake Ridge at any time between 45 and 35ka. This is fundamentally different from the hydrographic situation during the Holocene where NADW extends below 4500m at this location. The eopenNd of past deep water recorded in the Blake Ridge sediments was least radiogenic during Dansgaard/Oeschger (D/O) Interstadial (IS) 8 (eopenNd=-11.3) and most radiogenic immediately preceding IS 9 (eopenNd=-9.8). More radiogenic compositions were also recorded during H4 (-10.2≤eopenNd≤-9.9). The Nd isotope variability in MIS 3 matches that of a physical bottom current strength reconstruction from the same location. Neither record follows the pattern of Northern Hemisphere D/O climatic cycles. In our record, reduced mixing with northern source waters started in stadial 12 and lasted until after H4 in stadial 9, followed by a rapid increase in NSW contribution thereafter. This major change in the Nd isotope record predates the iceberg discharge event Heinrich 4 by more than 3ka indicating a shallowing of the water mass boundary between Glacial North Atlantic Intermediate Water and Southern Source Water beneath. This early change in bottom water properties at the deep Blake Ridge suggests that North Atlantic deep water advection may already have decreased several thousand years before the actual iceberg discharge event and associated freshening of the surface waters in the North Atlantic. The change can thus not be attributed to climatic events in the North Atlantic but may be related to changes in flux of deep water from the South. © 2010 Elsevier Ltd.